Effect of turf on the cutting movement of female football players - Strutzenberger, G.; Cao, H.-M.; Koussev, J.; Potthast, W.; Irwin, G. (Journal of Sport and Health Science, 2014)
Purpose: The globalisation of artificial turf and the increase in player participation has driven the need to examine injury risk in the sport of football. The purpose of this study was to investigate the surface-player interaction in female football players between natural and artificial turf. Methods: Eight university level female football players performed an unanticipated cutting manoeuvre at an angle of 30° and 60°, on a regulation natural grass pitch (NT) and a 3G artificial turf pitch (AT). An automated active maker system (CodaSport CXS System, 200 Hz) quantified 3D joint angles at the ankle and knee during the early deceleration phase of the cutting, defined from foot strike to weight acceptance at 20% of the stance phase. Differences were statistically examined using a two-way (cutting angle, surface) ANOVA, with an a level of p < 0.05 and Cohen's d effect size reported. Results: A trend was observed on the AT, with a reduction in knee valgus and internal rotation, suggesting a reduced risk of knee injury. This findings highlight that AT is no worse than NT and may have the potential to reduce the risk of knee injury. The ankle joint during foot strike showed large effects for an increase dorsiflexion and inversion on AT. A large effect for an increase during weight acceptance was observed for ankle inversion and external rotation on AT. Conclusion: These findings provide some support for the use of AT in female football, with no evidence to suggests that there is an increased risk of injury when performing on an artificial turf. The ankle response was less clear and further research is warranted. This initial study provides a platform for more detailed analysis, and highlights the importance of exploring the biomechanical changes in performance and injury risk with the introduction of AT.